National historical narratives in online newspapers: collective memories of troubled colonial past in Spain - César López Rodríguez; Germán Dorado Cazorla (Panta rei, 2025)
National narratives play a central role in historical knowledge. These narratives usually convey a favourable moral view of the nation's actions in the past. This study analyses the narratives produced about the so-called Discovery and Conquest of America, through Spain's four most-read online newspapers. Using content analysis, a sample of 200 articles was examined. This study investigated the nation's role as a historical subject, the moral judgments involving the nation, and the exoneration strategies used to justify misdeeds. The nation appeared as the main historical subject, reinforcing an essentialist conception. Results revealed differences in judging the nation depending on the political orientation of the media. Conservative newspapers associated with a conservative political ideology displayed a traditional national narrative, with a predominance of positive views and frequent exoneration strategies to bolster the nation's image. Finally, the role of these representations in teaching history and developing historical thinking is discussed.